Intracranial endodermal cyst presenting with nonobstructive hydrocephalus: A case report. Issue 6 (February 2019) - Fujii, Yoshiko; Nagaishi, Masaya; Nakae, Ryuta; Takigawa, Tomoji; Tanaka, Yoshihiro; Suzuki, Kensuke
Abstract: Rationale: Endodermal cysts are rare benign lesions in the central nervous system. Their common symptoms include headache and neck pain caused by mass effect or inflammatory reaction. We report the case of an elderly woman with intracranial endodermal cyst who presented with nonobstructive hydrocephalus. Patient concerns: A 78-year-old woman presented with acute deterioration of consciousness caused by acute hydrocephalus. She subsequently underwent ventriculoperitoneal shunt placement. Eighteen months after this operation, she developed numbness of extremities and gait and progressive cognitive disturbances. Diagnosis: Initially, the endodermal cyst could not be recognized, but it became clinically evident in the craniocervical junction after ventriculoperitoneal shunt placement. MRI revealed multiple cystic lesions in the pontomedullary cistern. Postoperative pathology confirmed the diagnosis of endodermal cyst. Interventions: Subtotal resection of the cystic lesion was performed. Intra-operatively, multiple cysts containing a milky white fluid were noted and the medullary surface including the median and lateral apertures of the fourth ventricle were covered by thick, cloudy arachnoid membrane. Outcomes: Although the numbness of extremities improved after the surgery, she remained bedridden due to deterioration in cognitive function and generalized muscle weakness. The patient developed recurrence 2 months after the surgery; however, no additional surgery was performed owing to her poor general condition. Lessons: Endodermal cysts rarely present with nonobstructive hydrocephalus caused by recurrent meningitis. In such cases, the lesions are often invisible on initial diagnostic imaging, and complete resection of the lesions is typically difficult because of strong adhesion between the cyst walls and contiguous vital structures.